Analisis penerapan perhitungan pajak penghasilan badan menurut undang- undang republik indonesia nomor 36 tahun 2008 - Evan Firdaus; Dady Nurpadi; Dwi Tianingsih (Jurnal Riset Manajemen Indonesia, 2023)
The purpose of this study is to find out how to apply the calculation of Corporate Income Tax according to Law Number 36 of 2008. The type of research used is descriptive and comparative analysis research by collecting all data and then processing, analyzing, and researching further and then drawing conclusions. The technique of data collected is based on observation, interviews, documentation and literature study. The results of this study conclude that the calculation of PPh of the Kokardan KPRI Agency according to PP No. 23 of 2018 is Rp. 9,977,044.00, in 2020 it is Rp. 12,373,382.00 and in 2021 it is Rp. 9,236,823.00. Meanwhile, according to Law No. 36 of 2008 it was Rp. 86,366,609.88 in 2019, Rp. 102,230,674.37 in 2020 and Rp. 72,143,916.46 in 2021. KPRI Kokardan must perform calculations by calculating PKP, namely gross circulation minus costs, calculating income tax payable for one tax year, namely 2019 by 50% x 25% xPKP and 2020-2021 by 50% x 22% xPKP.